2018
DOI: 10.1149/2.0541811jes
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Bis(2,2,2-trifluoroethyl)phosphate Li[O2P(OCH2CF3)2]: A High Voltage Additive for LNMO/Graphite Cells

Abstract: The fluorinated phosphate lithium bis (2,2,2-trifluoroethyl) phosphate (LiBFEP) has been investigated as a film-forming additive employed to passivate the cathode and hinder continuous oxidation of the electrolyte. Cyclic voltammetry (CV) and linear sweep voltammetry coupled with online electrochemical mass spectrometry (LSV-OEMS) on a conductive carbon electrode (i.e., a C65/PVDF composite) showed that LiBFEP decreases electrolyte oxidation (CV and LSV) and LiPF 6 decomposition at high potentials. Incorporati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 48 publications
2
27
0
Order By: Relevance
“…Incorporation of additives into electrolyte formulations can result in the improved performance of LNMO/graphite cells. The specific functions of the additives include scavenging corrosive acid species such as HF or phosphorus pentafluoride (PF 5 ) or the generation of a passivation film, the surface film on the electrode, depending on the functional groups in the additives. It was reported that siloxane derivatives such as silyl groups (Si–O) can capture HF or H 2 O to form silicon fluorides (Si–F). ,, Lithium phosphate derivatives such as lithium difluorophosphate and lithium dimethyl phosphate (LiDMP) were reported to improve the cycling and rate performances of NCM/graphite cells by modifying the chemical composition of SEI layers on graphite electrodes. , Moreover, the additives can have more than one mode of performance enhancement, when they possess multiple types of functional groups. , …”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of additives into electrolyte formulations can result in the improved performance of LNMO/graphite cells. The specific functions of the additives include scavenging corrosive acid species such as HF or phosphorus pentafluoride (PF 5 ) or the generation of a passivation film, the surface film on the electrode, depending on the functional groups in the additives. It was reported that siloxane derivatives such as silyl groups (Si–O) can capture HF or H 2 O to form silicon fluorides (Si–F). ,, Lithium phosphate derivatives such as lithium difluorophosphate and lithium dimethyl phosphate (LiDMP) were reported to improve the cycling and rate performances of NCM/graphite cells by modifying the chemical composition of SEI layers on graphite electrodes. , Moreover, the additives can have more than one mode of performance enhancement, when they possess multiple types of functional groups. , …”
Section: Introductionmentioning
confidence: 99%
“…For carbonate electrolyte based batteries, the decomposition of electrolyte causes the evolution of gases that lead to the expansion of the cell. [ 3,4 ] The evolution of gases is one of the indications of the instability of electrolytes due to the electrode–electrolyte interfacial reactions. Different approaches designed to investigate the gas evolution along with interfacial reactions include Archimedes’ in situ gas analyzer [ 5 ] and ex situ GC‐MS [ 6 ] via LMBs and Li‐ion batteries (LIBs).…”
Section: Introductionmentioning
confidence: 99%
“…[ 6–9 ] It has been reported that the interfacial reactions upon charging of Li/NMC and graphite/NMC cells with carbonate electrolytes generate CO 2 , CO, H 2 and C 2 H 4 gases. [ 3,7,9–13 ] Nevertheless, the main source of hydrogen (H 2 ) gas at the early stage of solid–electrolyte‐interphase (SEI) formation is the reduction of residual trace H 2 O at the anode surface with the formula of H 2 O + e − → OH − + ½ H 2 . [ 7,8,14 ]…”
Section: Introductionmentioning
confidence: 99%
“…As shown, an excellent performance with a capacity retention of ∼90% is achieved after 300 cycles. This is one of the best performances ever reported at such a high mass loading for the high-voltage LNMO spinel. , The CEs are plotted in Figure b; the cell exhibits an average CE of 99.45%, implying that the lithium inventory loss is suppressed. Notably, the cell impedance growth is negligible, as depicted in Figure c.…”
Section: Results and Discussionmentioning
confidence: 86%